Complete Correction of Brain and Spinal Cord Pathology in Metachromatic Leukodystrophy Mice - Audouard, Emilie; Oger, Valentin; Meha, Béatrix; Cartier, Nathalie; Sevin, Caroline; Piguet, Françoise (Frontiers in Molecular Neuroscience, 2021)
Metachromatic leukodystrophy (MLD) is a lysosomal storage disorder characterized by accumulation of sulfatides in both glial cells and neurons. MLD results from an inherited deficiency of arylsulfatase A (ARSA) and myelin degeneration in the central and peripheral nervous systems. Currently, no effective treatment is available for the most frequent late infantile (LI) form of MLD after symptom onset. The LI form results in rapid neurological degradation and early death. ARSA enzyme must be rapidly and efficiently delivered to brain and spinal cord oligodendrocytes of patients with LI MLD in order to potentially stop the progression of the disease. We previously showed that brain gene therapy with adeno-associated virus serotype rh10 (AAVrh10) driving the expression of human ARSA cDNA alleviated most long-term disease manifestations in MLD mice but was not sufficient in MLD patient to improve disease progression. Herein, we evaluated the short-term effects of intravenous AAVPHP.eB delivery driving the expression of human ARSA cDNA under the control of the cytomegalovirus/b-actin hybrid (CAG) promoter in 6-month-old MLD mice that already show marked sulfatide accumulation and brain pathology. Within 3 months, a single intravenous injection of AAVPHP.eB-hARSA-HA resulted in correction of brain and spinal cord sulfatide storage, and improvement of astrogliosis and microgliosis in brain and spinal cord of treated animals. These results strongly support to consider the use of AAVPHP.eB-hARSA vector for intravenous gene therapy in symptomatic rapidly progressing forms of MLD.